GAMBARAN KOLABORASI TENAGA KESEHATAN DALAM ANC TERPADU DENGAN TINGKAT KEPUASAN IBU DI PUSKESMAS OEPOI KUPANG - Vinsen Belawa Making (CHMK MIDWIFERY SCIENTIFIC JOURNAL, 2019)
ABSTRACT Background. LBW is still a public health problem in many countries, because it is considered to be one of the factors causing infant mortality. Quality ANC is one of the factors preventing LBW and therefore good collaboration is needed between health workers. Oepoi Community Health Center (Puskesmas) is the lowest puskesmas with only 1.1% compared to other puskesmas in Kupang City. Therefore, research related to collaboration in the Puskesmas was taken. Objective. The purpose of this study was to find out the description of collaboration of health workers with maternal satisfaction levels in integrated ANC at Puskesmas Oepoi. Method. This type of research is purely qualitative with an inductive approach. The total sample was 40 people consisting of 33 pregnant women and 7 health workers. Location: Oepoi Health Center. Time: March - June 2018. Results. The results of this study illustrate the incidence of LBW in Oepoi Health Center (Puskesmas Oepoi) has the lowest percentage among all Puskesmas in Kupang City with only 13 cases (1.1%). ANC management of 33 respondents found a distribution of respondents with good ANC management as many as 33 people (100%). ANC Collaboration Implementation from 7 respondents found all respondents stated Collaboration had gone well. This is directly proportional to the level of satisfaction of pregnant women, namely; very satisfied as many as 25 people or 75%, the remaining 25% said they were satisfied and no one expressed dissatisfaction. This means that Oepoi Health Center succeeded in suppressing LBW. Conclusion. Conclusion of the study that the collaboration of health workers in integrated ANC conducted by health workers at the Oepoi Health Center was good with a good level of patient satisfaction. This is also the reason why the percentage of LBW in Oepoi Community Health Center is very low. As a suggestion, this collaboration model can be adopted by other puskesmas and further research is needed to strengthen this model. Keywords: Integrated ANC Collaboration